The Risk of Thromboembolism in Asymptomatic Patients with Protein C and Protein S Deficiency: A Prospective Cohort Study - Pabinger, Ingrid; Kyrle, Paul A; Heistinger, Max; Eichinger, Sabine; Wittmann, Eva; Lechner, Klaus (Thrombosis and Haemostasis, 1994)
Background: Prospective studies on the incidence of thrombosis in asymptomatic individuals with hereditary protein C- or protein S deficiency have not been performed so far.Objective: We have carried out a prospective cohort study in 44 asymptomatic protein C- and protein S deficient subjects and in 49 asymptomatic non-deficient relatives (age at study entry > 14 years) of symptomatic deficient patients.Methods: 20 asymptomatic protein C deficient (median age 20 years) and 24 asymptomatic protein S deficient patients (median age 21.5 years) were prospectively followed and compared with 20 asymptomatic non-deficient relatives (median age 25 years) of protein C- and 29 (median age 27 years) of protein S deficient patients. The total observation period was 118.8 patient years for protein C deficient and 92.8 for protein S deficient patients. Patients were not on anticoagulants except for short duration in case of high risk situations.Results: Eight thromboembolic events (1 pulmonary embolism, 1 deep vein thrombosis + pulmonary embolism, 3 deep vein thrombosis, 1 caval vein thrombosis and 2 superficial vein thrombosis) occurred in 6 deficient patients. The incidence of thromboembolism was 2.5% per patient year for protein C deficient and 3.5% per patient year for protein S deficient patients. 4 events occurred spontaneously, in 2 patients thromboembolic events were triggered by high risk situations (caesarean section, minor trauma). In the controls no thromboembolic events occurred. The probability for thromboembolism was significantly higher in protein C and protein S deficient patients compared to the control group (Wilcoxon test, p = 0.002, log rank test, p = 0.001). One major and 5 minor uneventful surgeries were carried out in the deficient patients using heparin prophylaxis. 1/8 pregnancies was complicated by superficial vein thrombosis during the second trimester despite prophylactic heparin administration. The same pregnancy was complicated by pulmonary embolism 5 weeks after delivery after discontinuation of heparin.Conclusions: Asymptomatic deficient relatives of symptomatic patients with protein C or protein S deficiency are at an increased risk of thrombosis compared to nondeficient individuals. Prophylactic treatment seems to be highly effective in high risk situations.